Unfavourable results in temporomandibular joint ankylosis surgery - Mukund Jagannathan; Amarnath V. Munoli (Indian Journal of Plastic Surgery)
Temporomandibular joint (TMJ) ankylosis is a debilitating condition usually afflicting children and young adults. Treatment is surgical, i.e., release of the ankylosed joint/s with or without interposition arthroplasty and correction of secondary deformities (mandibular retrusion and asymmetry) This article deals with identifying potential setbacks in TMJ ankylosis surgery and preventing them.